Clinical and biometrical evaluation of socket preservation using demineralized freeze-dried bone allograft with and without the palatal connective tissue as a biologic membrane - Hamid Moghaddas; Mohammad Reza Amjadi; Narges Naghsh (Wolters Kluwer Medknow Publications, 2012)
Background: Alveolar ridge preservation following tooth extraction has the ability to maintain the ridge dimensions and allow the implant placement in an ideal position fulfilling both functional and aesthetic results. The aim of this study was to evaluate the efficacy of the palatal connective tissue as a biological membrane for socket preservation with demineralized freeze-dried bone allograft (DFDBA). Materials and Methods: Twelve extraction sites were treated with DFDBA with (case group) and without (control group) using autogenous palatal connective tissue membrane before placement of implants. Alveolar width and height, amount of keratinized tissue, and gingival level were measured at pre-determined points using a surgical stent at two times, the time of socket preservation surgery and 4 months later during implantation. The significance level was set at 0.05. Results: In both groups a decrease in all socket dimensions was found. The average decrease in socket width, height, keratinized tissue, and gingival level in case group was 1.16, 0.72, 3.58, and 1.27 mm, and in control group was 2.08, 0.86, 4.52, and 1.58 mm respectively. Statistical analysis showed that decrease in socket width ( P = 0.012), keratinized tissue ( P ≤ 0.001), and gingival level ( P = 0.031) in case group was significantly lower than that of the control group. Results showed no meaningful difference in socket height changes when compared with case and control groups ( P = 0.148). Conclusion: Under the limits of this study, connective tissue membrane could preserve socket width, amount of keratinized tissue, and the gingival level more effectively than DFDBA alone.